The triangle of microfinance: Financial sustainability, outreach, and impact - Zeller, Manfred; Meyer, Richard L. (Johns Hopkins University Press, 2002)
The initial success of microfinance programs in the 1970s led pioneers to think that many essential problems of the poor might be resolved by access to credit alone -- the ability to acquire assets, to start businesses, to finance emergency needs and to insure against illness and disaster. Part of that vision has certainly been realized. But much remains to be done. Most microfinance institutions (MFIs) are still small and vulnerable to constraints on their resources and to the risks inherent in single-issue portfolios. Most depend upon donors and governments to remain in operation. There is much waste and duplication, and some mature programs have declining loan recovery rates, even as competition for borrowers rises from conventional banks and finance companies. Analyzing the failures of credit programs aimed at small farmers and the successes of other programs showed the need for new understanding of the ways that poor households make spending, borrowing, and saving decisions. This area was previously neglected in policymaking on food security issues. The International Food Policy Research Institute (IFPRI) supported household surveys in nine Asian and African countries during the 1990s that analyzed formal and informal financial transactions, and it also evaluated the success of innovative approaches at some MFIs. The overall goal was to clarify the conditions under which state investment in microfinance programs might improve life for poor people more than state investment of the same funds in education, health, nutrition, or infrastructure development. The research led to the concept of the critical triangle of microfinance" -- the need for any MFI to manage simultaneously the problems of outreach (reaching the poor both in terms of numbers and depth of poverty), financial sustainability (meeting operating and financial costs over the long term), and impact (having discernible effect upon clients' quality of life). This book elaborates on these objectives and shows that the most successful MFIs expand all sides of that triangle. Tradeoffs are sometimes inevitable, but even so, synergies among the three make the concept valuable -- from Author's Abstract."